# trig

posted by .

Prove (cscx+cotx)(cscx-cotx)=1

## Similar Questions

1. ### calculus

express in sinx 1 1 ---------- + -------- cscx + cotx cscx - cotx and express in cosx 1 + cot x ------- - sin^2x cscx = 1/sinx so what do i do w. that extra one on the top!?
2. ### trig

express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is that right?
3. ### Trig

Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (x=theta BTW)
4. ### drwls

My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) = (sinx/cosx)*cotx*(1/sinx) "The last steps should be obvious" Not to me. I can convert (sinx/cosx) to …
5. ### Precalculus

Simplify:[(cscx-cotx)(cscx+cotx)]/cscx
6. ### Math

prove:(cscx-cotx)^4 x (cscx+cotx)^4 = 1
7. ### Trigonometry

prove:(cscx-cotx)^4 x (cscx+cotx)^4 = 1
8. ### ap calc bc

hi! ok, i know that deriv(cscx) = -cscxcotx and that deriv(cos) = -sinx deriv(cotx) = -((cscx)^2) my question is: is this (statements below) correct?
9. ### Trig

prove (cscx-secx/cscx+secx)=(cotx-1/cotx+1)
10. ### Precalculus/Trig

I can't seem to prove these trig identities and would really appreciate help: 1. cosx + 1/sin^3x = cscx/1 - cosx I changed the 1: cosx/sin^3x + sin^3x/sin^3x = cscx/1-cosx Simplified: cosx + sin^3x/sin^3x = cscx/1-cosx I don't know …

More Similar Questions